Topologically associating domains and their long-range contacts are established during early G1 coincident with the establishment of the replication-timing program - Dileep, Vishnu; Ay, Ferhat; Sima, Jiao; Vera, Daniel L.; Noble, William S.; Gilbert, David M.

(untitled) (Genome Research, 2015)
Mammalian genomes are partitioned into domains that replicate in a defined temporal order. These domains can replicate at similar times in all cell types (constitutive) or at cell type-specific times (developmental). Genome-wide chromatin conformation capture (Hi-C) has revealed sub-megabase topologically associating domains (TADs), which are the structural counterparts of replication domains. Hi-C also segregates inter-TAD contacts into defined 3D spatial compartments that align precisely to genome-wide replication timing profiles. Determinants of the replication-timing program are re-established during early G1 phase of each cell cycle and lost in G2 phase, but it is not known when TAD structure and inter-TAD contacts are re-established after their elimination during mitosis. Here, we use multiplexed 4C-seq to study dynamic changes in chromatin organization during early G1. We find that both establishment of TADs and their compartmentalization occur during early G1, within the same time frame as establishment of the replication-timing program. Once established, this 3D organization is preserved either after withdrawal into quiescence or for the remainder of interphase including G2 phase, implying 3D structure is not sufficient to maintain replication timing. Finally, we find that developmental domains are less well compartmentalized than constitutive domains and display chromatin properties that distinguish them from early and late constitutive domains. Overall, this study uncovers a strong connection between chromatin re-organization during G1, establishment of replication timing, and its developmental control.